Effect of IL12A and IL12B polymorphisms on the risk of Chlamydia trachomatis-induced tubal factor infertility and disease severity. - Ohman, H; Bailey, R; Natividad, A; Ragoussis, J; Johnson, L; Tiitinen, A; Halttunen, M; Paavonen, J; Surcel, H (2012)
BACKGROUND: Interleukin-12 (IL-12) and related cytokines induce activation and differentiation of T cells. Our aim was to investigate the associations between genetic differences in IL-12-family cytokines and the pathogenesis of chlamydial disease. METHODS: The final study population consisted of 100 women with Chlamydia trachomatis-induced tubal factor infertility (TFI) and 125 pregnant women as controls. Three single nucleotide polymorphisms (SNPs) of IL12A and seven SNPs of IL12B genes were determined from isolated DNA using the Sequenom system with matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry. RESULTS: We found that the IL12B SNP rs3212227 was associated with both susceptibility and severity of TFI. The minor allele C was rare and only one CC homozygote was found among the controls. AC heterozygotes were more common among TFI cases than among controls (P = 0.009) and were associated with increased risk of TFI [odds ratios (OR) = 2.44, 95% confidence intervals (CI) = 1.23-4.87]. Carrying the minor allele C was also associated with disease severity (P for trend = 0.008) and moderate (OR = 2.51, 95% CI = 1.06-5.95) and severe tubal damage (OR = 2.73, 95% CI = 1.15-6.52). CONCLUSIONS: The results suggest that variation in the IL12B gene partly explains inter-individual differences in disease susceptibility and severity.